Penerapan Usability pada Aplikasi PENTAS Dengan Menggunakan Metode System Usability Scale (SUS) - Ade Saputra (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Assessment Test is one of the routine agenda that is carried out every semester change. This test is conducted to see the development of students in learning activities. Currently SMK 5 Kota Tangerang already uses a mobile application using the PENTAS application in answering the exam questions. But this application needs to be done to understand applications that can be used properly, or vice versa. This study uses the System Usability Scale (SUS) method to measure the use of this application for use. This SUS method has 10 questions that will be answered by respondents who are directly involved in using the PENTAS application. The average score obtained by the System Use Scale method is 46.00. These results fall into the Unacceptable category, so this PENTAS application is not good for use.